Using participatory research to co-produce an education and training e-resource to support care home staff to meet the sexuality, intimacy and relationship needs of care home residents with and without dementia - Horne, Maria; Youell, Jane; Brown Wilson, Christine; Brown, Laura; Simpson, Paul; Dickinson, Tommy (Frontiers in Dementia, 2023)
Aim: To present the methodological approach and research methods chosen in a research study designed to enable the collaborative creation of an education and training e-resource designed to facilitate and support care home staff to address the sexuality, intimacy and relationship needs of older care home residents.Design: Co-production using community-based participatory approach.Methods: Four participatory workshops with care home staff, residents and their significant others.Results: Workshops 1 and 2 identified and developed real-world case scenarios related to sexuality, intimacy and relationship needs and identified care staff training needs in this area. Then workshop 3 provided valuable feedback on the prototype training e-resource, and the final workshop identified care home staff engagement with and implementation of the e-resource in practice. This is a provisional file, not the final typeset articleThe findings provide evidence that using participatory approaches, such as coproduction, to develop education and training resources in a sensitive subject area with care home residents, significant others, carers and care home staff, was a useful approach in engaging a vulnerable population group, in a sensitive area. However, this approach is not without challenges in care home communities.